Theory-Informed Course Design: Applications of Bloom's Taxonomy in Undergraduate Public Health Courses. (March 2022) - Callaghan-Koru, Jennifer A.; Aqil, Anushka R.
The public health workforce needs an array of knowledge and skills to effectively address current and future public health challenges. While existing competency models establish educational objectives for public health degree programs, there is insufficient guidance on how academic programs should develop these competencies, and workforce assessments continue to identify skills gaps in areas such as critical thinking and problem analysis. In this article, we describe an approach for designing undergraduate public health courses based on the hierarchy of cognitive processes in Bloom's taxonomy. Course activities are sequenced to provide students with opportunities to attain increasing mastery of course concepts and analytical skills, from remembering new concepts to applying them in case studies and creating original analyses and proposals. This simple approach has been applied to three separate courses taught by multiple instructors over 3 years and has received positive feedback from students. By explicitly communicating the theoretical basis for course activities, this approach also promotes metacognitive knowledge in students that can foster their continued learning success.